ANALISIS PENGARUH FRAUD PENTAGON MODEL DALAM MEMPREDIKSI KETERJADIAN FRAUDULENT FINANCIAL STATEMENT (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2016-2018) - Farrah Geubrina Rezeki (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
This study aims to determine the effect of Fraud Pentagon Model to predicting occurrence of Fraudulent Financial Statements in manufacturing companies listed on the Indonesia Stock Exchange in 2016-2018. Pentagon Fraud Model is a development of Fraud Triangle Theory and Fraud Diamond, including opportunity, pressure, competence, rationalization, and arrogance. The sample consisted of 83 manufacturing companies listed on the Indonesia Stock Exchange in 2016-2018, selected using purposive sampling method. The data analysis method used is multiple regression with SPSS version 25.0. The results of this study indicate that pressure and arrogance influence in predicting the occurrence of Fraudulent Financial Statements. While rationalization, opportunity, and competence have no effect in predicting occurrence of Fraudulent Financial Statements.